Treatment for identical twins simultaneously developing an eating disorder precipitated by COVID-19 pandemic home quarantine - Pang, Nicholas Tze Ping; Lee, Sze Chet; Ng, Chun Keat; Hii, Jia Wen; Mohd Amiruddin Mohd Kassim (Medical Communications, 2020)
An eating disorder presenting simultaneously in identical twins remains a rarity in the literature. In this case report, we describe monozygotic twins who presented simultaneously with anorexia nervosa as a psychological effect of COVID-19 home quarantine. Both twins were previously well but developed food restriction, exercise, and mutual surveillance behaviours in competition with each other over three months in early 2020. There were no features of other mood, anxiety or psychotic disorders, and there was no organic disease. However, a strong family history of anxiety disorders and highly permeable familial boundaries were identified. Non-pharmacological management modalities including family therapy and psychotherapy were implemented, and tailored to the twins. We discuss the unique genetic and psychological interactions that conceivably explain the aetiology of this simultaneous presentation of an eating disorder in a pair of twins and examine a simple psychodynamic formulation of this simultaneous emergence. Lastly, we look at the sequelae of COVID-19 related quarantines and isolation as potentiators of eating disorders in adolescents whose education and potential employment were drastically curtailed by movement restrictions.